« Hermetismo »: un muestrario - Martín Arias (Cuadernos LIRICO)
Taking as a starting point a set of occurrences of the words « hermetic » and « hermeticism » in contemporary Argentine literature and literary criticism, this article aims at exploring the uses of those terms in Tamara Kamensain’s essay Una intimidad inofensiva. Los que escriben con lo que hay (2016), and a review of Milita Molina’s Los sospechados (2002) by Martín Kohan. After assessing the relation between those uses and the one that Héctor Libertella made of the same words, this article postulates a series of connections and disconnections between writing, thought, obscurity and transparency in Argentine literature.